PENGARUH UMUR PERUSAHAAN, PROFITABILITAS, LAVERAGE, UKURAN PERUSAHAAN TERHADAP TAX AVOIDANCE PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Novelia Handayani Saragih; Nia Angelia; Jhon Lismart Benget. P.; Merry Rusida S; Audrey M Siahaan (Akuntansi Prima, 2024)
Tax avoidance is one of the efforts to minimize the tax burden that is often done by companies. There are several factors that affect a company in conducting tax avoidance including, company age, profitability, leverage and company size. This study used a quantitative approach. Quantitative data regarding information about the variables studied in the form of numbers or numbers, it can be concluded that the age of the company, profitability, laverage, company size affect the tax avoidance variable simultaneously. The study selected 10 companies as samples during 2018-2021. Therefore, the number of observations obtained is 40 observations. The results of this research analysis can be concluded that company age, profitability, laverage, company size have a positive effect on tax avoidance.